Crypto-currency: Is the future dark or bright?. Issue 5 (4th July 2019) - Yousuf Javed, Mohd.; Husain, Rehan; Khan, Bilal Mustafa; Azam, Mohammad Khalid
Abstract: Purpose: This study reviews the research work that has been carried out in the field of cryptocurrency (cc) and financial risk during past five years ( 2013-2018 ).This paper tracks and reviews the research work publish in leading academic journal in above mentioned journal. It then reviews from pragmatic and methodological approach. Design methodology and approach: this study analyses the selected contribution from the perspective of "Financial risk in cryptocurrency." And further compares various studies on the article type and methodologies and research designs used in them. Using relational analysis approach recurrent themes are identified and research clusters are formed. Findings: The analysis leads to the identification of the major parameters namely: Financial risk, market risk, liquidity risk and operational risk and these rea the parameters that are impacting the values of cryptocurrency. We have also analysed the issues and challenges in the cryptocurrency market of India. Implications: We have tried to propose a model and collected the information from various reports and papers. We have also find out that various risk which are associated with CC market are controllable in nature on the other hand some of them are uncontrollable in nature. Originality value: Most reviews rely on bibliometric analysis or simple thematic analysis for literature review. This study provides greater insights by using a research paradigm framework to categorize and summarize the literature. This approach provides a comprehensive yet concise picture of the literature to future researchers. Paper type: Research type